PENGARUH CELEBRITY ENDORSER DAN BRAND IMAGE TERHADAP PEMBELIAN MIE LEMONILO OLEH FANS CLUB KPOP ARMY SOLO - Erna Nuzulul Wakhid; Kusna Djati Punama (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to determine the influence of Celebrity Endorser and Brand Image on purchasing decisions. The research method employed is quantitative, with a sample size of 224 members from the K-Pop Army Solo fan club. Data collection is conducted through a questionnaire, and the sampling method utilizes the Slovin Formula with Accidental Sampling technique. Data analysis is performed using multiple linear regression analysis with the assistance of SPSS.The results of the research indicate that Celebrity Endorser and Brand Image have a significant positive influence on the purchasing decisions of Mie Lemonilo among K-Pop enthusiasts, particularly within the Army Solo fan club. The coefficient of determination is 44.3%, indicating that the variability in purchasing decisions can be explained by the tested regression model, while the remaining variance is influenced by other factors not included in this study.